Communication Strategies of the Four INLA Renewal Movements in Internalizing the New Moral Values ​​of 'One Family World': A Case Study of INLA Goes to School in Batam City - Putri, Eka Wijaya; Lusianawati, Hayu (West Science Social and Humanities Studies, 2026)
This study aims to analyze the communication strategies of the Four INLA Renewal Movements in internalizing the moral values ​​of "One Family World" through the INLA Goes to School program in Batam City. This study uses a qualitative approach with a case study method. Data collection techniques were carried out through in-depth interviews, observations, and documentation of INLA administrators, program facilitators, and school officials. The results show that INLA implements educational, persuasive, and participatory communication strategies by placing aesthetic communication as the main approach. Elements of art, movement, music, stories, symbols, and emotional expressions are used to build students' moral experiences. The Four INLA Renewal Movements—renewal of mindsets, attitudes and behaviors, social relations, and culture and the environment—form an integrated communication framework. This study concludes that aesthetic communication plays a strategic role in internalizing moral values ​​because it is able to reach the cognitive, affective, and behavioral aspects of students, although there are still limitations in the aspects of sustainability and long-term impact evaluation.